(untitled) (Revista Electrónica REDINE, 2024)
Accompanying the family in the transitions that its members go through throughout their life cycle is an increasingly present requirement given the social dynamism and the emergence of new challenges related to coexistence. This essay, as a result of documentary research, shows an approach to the conceptualization of family orientation and then lists a series of strategies from which to consolidate the psychosocial well-being of parents and children. In conclusion, achieving the functional and multidimensional balance of the family requires strategic advisory actions that help with the definition of roles, overcoming the crisis and the adoption of both healthy and positive parenting styles.